Answer:
Hopes this helps
Step-by-step explanation:
Simplifying
10 + -13x = -8x + 25
Reorder the terms:
10 + -13x = 25 + -8x
Solving
10 + -13x = 25 + -8x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8x' to each side of the equation.
10 + -13x + 8x = 25 + -8x + 8x
Combine like terms: -13x + 8x = -5x
10 + -5x = 25 + -8x + 8x
Combine like terms: -8x + 8x = 0
10 + -5x = 25 + 0
10 + -5x = 25
Add '-10' to each side of the equation.
10 + -10 + -5x = 25 + -10
Combine like terms: 10 + -10 = 0
0 + -5x = 25 + -10
-5x = 25 + -10
Combine like terms: 25 + -10 = 15
-5x = 15
Divide each side by '-5'.
x = -3
Simplifying
x = -3